Privatization Of The Education Sector In Indonesia: A Review Of Conflict Theory - Hidayati Hidayati; Resti Amalia; Ririn Septia; M. Aries Taufiq (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
Privatization of education in Indonesia is legitimized by a number of regulations, for example Law no. 20 of 2003 on the National Education System and Law no. 9 on Education Legal Entities. The existence of this education legal entity makes educational institutions free to seek capital to invest in educational activities. So that the world of education turns into a commercial investment land. This condition, in the view of sociology, will lead to interclass conflicts caused by the inequality of the community in accessing education. This study aims to describe the views of conflict theory regarding the phenomenon of privatization of education. The method used is the study of literature or literature by collecting secondary data from books, news and journal articles. The results of the study show that 1) the conflict theory view of education privatization can be viewed from the community analysis unit and the individual analysis unit; 2) At the level of the community unit of analysis, education privatization can be explained through Karl Marx's conflict theory and Weber's theory of power. 3) Marx's conflict theory emphasizes the two social classes formed due to differences in ownership of capital production factors. Meanwhile, according to Weber, the process of conflict is caused by the existence of authority or power that separates society into superordinate groups and subordinate groups. 4) At the individual unit of analysis level, conflicts due to education privatization can be viewed from Coser's conflict theory, where conflicts do not only have a negative impact, but also a positive impact on society.